Adverse Childhood Experiences and Police Contact in Canada - Testa, Alexander (Journal of interpersonal violence, 2025)
A growing body of research has demonstrated that adverse childhood experiences (ACEs) are a risk factor for criminal justice system contact. However, much of this research is limited by (1) being conducted in the United States and (2) a lack of details on specific types of harmful experiences of criminal justice system contact, such as police contact characterized by intrusion or harassment. Using survey data from 940 individuals aged 16 to 30 in Canada from the Canadian Study of Adolescent Health Behaviors, this study investigates the relationship between ACEs and police contact, focusing on encounters involving intrusion or harassment. Results from logistic and multinomial logistic regression analyses reveal that individuals with high ACE exposure, particularly those with four or more ACEs, are more likely to have police contact, including experiences of intrusion and harassment. The results are significant in understanding the interplay between childhood trauma and later encounters with the criminal justice system, emphasizing the need for trauma-informed approaches in policing and healthcare. The study highlights the importance of early interventions to mitigate the effects of ACEs and prevent adverse outcomes in police interactions.